Weevil resistant sweetpotato through biotechnology - International Potato Center (2012)
Sweetpotato weevils are responsible for significant losses of up to a third of the annual production in some sub-Saharan African (SSA) countries, threatening their food security. Biotechnology has been applied to introduce synthetic genes that produce proteins with activity against the weevils. A first group of such plants was tested but failed to display insecticidal activity. Quantification of the insecticidal protein in storage roots suggests that its accumulation is too low. More transgenic events are being screened to identify high expresser of the insecticidal protein. Correspondingly, two strategies have been commenced to fully control weevils. First, new synthetic genes are being developed with features reputed to enhance accumulation and functionality of the insecticidal protein. Second, a non-protein-based system is being developed to complement the insecticidal protein strategy in case weevil resistance is not ascertained.